1998
DOI: 10.1161/01.cir.98.14.1383
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Transient Outward Potassium Current Downregulation in Human Heart Failure

Abstract: These data provide further support for the hypothesis that Kv4.3 encodes all or part of the native cardiac Ito in humans and that part of the downregulation of this current in heart failure may be transcriptionally regulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
200
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 364 publications
(211 citation statements)
references
References 60 publications
9
200
0
2
Order By: Relevance
“…Indeed, the results presented here suggest that alterations in the functional expression of I to,f and I K1 channels with LVH do not reflect transcriptional or translational downregulation of the subunits encoding these channels, as has been previously suggested. 3,4,29 Rather, the results here suggest that although global transcriptional and translational machineries are acti-vated with LVH, 18 the expression of channel subunits do not increase corresponding to the increase in cell size. Therapeutic strategies aimed at reducing cellular hypertrophy or increasing the functional expression of repolarizing K ϩ channels would, therefore, appear to be promising approaches in the treatment of LVH-associated ventricular arrhythmias.…”
Section: Relationship To Previous Studiesmentioning
confidence: 53%
See 2 more Smart Citations
“…Indeed, the results presented here suggest that alterations in the functional expression of I to,f and I K1 channels with LVH do not reflect transcriptional or translational downregulation of the subunits encoding these channels, as has been previously suggested. 3,4,29 Rather, the results here suggest that although global transcriptional and translational machineries are acti-vated with LVH, 18 the expression of channel subunits do not increase corresponding to the increase in cell size. Therapeutic strategies aimed at reducing cellular hypertrophy or increasing the functional expression of repolarizing K ϩ channels would, therefore, appear to be promising approaches in the treatment of LVH-associated ventricular arrhythmias.…”
Section: Relationship To Previous Studiesmentioning
confidence: 53%
“…Reduced Kv current densities and action potential prolongation are consistent findings in experimental LVH models [3][4][5][6][7][8][9]11 and in failing human hearts. 10,29 The analyses completed here, however, revealed that cellular hypertrophy (increased C m ) is the main factor in determining reductions in I to,f and I K1 densities, because the mean amplitudes of these currents in TAC and sham LV cells were not significantly different. In contrast, mean I K,slow and I ss amplitudes were altered in TAC LV myocytes, suggesting that functional I K,slow and I ss channel expression is modulated with LVH.…”
Section: Marionneau Et Al Mechanisms Underlying K ؉ Current Remodelinmentioning
confidence: 57%
See 1 more Smart Citation
“…Western blot analyses of atrial and ventricular membrane proteins confirmed the presence of Kcna2 at 75 kDa in adult rat heart membranes 8. Furthermore, Kcna2 has also been observed in human ventricular tissue 5. Herein, Kcna2 RNA and protein expression was detected (Figure S2).…”
Section: Discussionmentioning
confidence: 67%
“…However, the molecular mechanisms underlying arrhythmias are still unknown 3. Delayed rectifier potassium channels are important for controlling the repolarization of several ion species in the heart, and decreases in the delayed rectifier potassium current (I K ) in heart failure results in action potential (AP) prolongation, which is an important contributor to the development of ventricular arrhythmias 4, 5, 6. Kcna2, also known as Kv1.2, which is a subunit of the voltage‐gated shaker channel family, is one of the dominant ion channels in cardiac muscle and encodes I K 7, 8.…”
Section: Introductionmentioning
confidence: 99%